Analisis Fundamental Makro, Struktur Modal Terhadap Nilai Perusahaan dengan Struktur Kepemilikan, Kinerja Keuangan dan Karakteristik Perusahaan sebagai Variabel Intervening pada Perusahaan Sub Sektor Kimia yang Terdaftar di BEI - Asari, Ayu; Hwihanus (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research aims to analyze the influence of macro fundamental analysis and capital structure on company value with ownership structure, financial performance and company characteristics as intervening variables in chemical sub-sector companies listed on the IDX. Macro fundamental analysis, capital structure, ownership structure, financial performance and company characteristics can influence company value. Signal Theory, Capital Structure Theory, and Agency Theory are the basis for this research. Company value, capital structure, macro fundamentals, ownership structure, financial performance, and company characteristics are important factors in determining company value. The results of the analysis show that several variables such as Macro Fundamentals, Company Characteristics, Financial Performance and Capital Structure have a significant influence on Company Value. However, there are also variables that are not significant such as Ownership Structure. Company value is an indicator of how the market assesses the company's current performance and future prospects, with Price to Book Value (PBV) used as one measure to describe the company's value. This research uses a quantitative approach with secondary data from chemical companies listed on the IDX. The implications of ownership for company value, capital structure and leverage on the financial performance of mining companies have also been discussed in related literature. These variables have a significant influence on company value, showing the importance of these factors in determining company value.